Exploring Innovation in Educational Services: A Case Study at a State Islamic University in Riau - Khairunsyah Purba; Nurmaini Dalimunte; Nelvi Rahmadani (STAI Hubbulwathan Duri, 2025)
Universities play a vital role in providing academic and administrative support services that facilitate student success. However, limitations in infrastructure, human resource capacity, and service delivery quality have hindered optimal educational support in many institutions. This study investigates how innovation in academic and instructional support is implemented at Sultan Syarif Kasim Islamic State University (UIN SUSKA) Riau. A qualitative descriptive approach was employed to explore institutional practices and leadership strategies in advancing educational services. Data were collected through in-depth interviews with key stakeholders, including the Rector, Head of PTIPD, faculty leaders, lecturers, and administrative staff. Additional data were gathered from institutional documents and observations. The findings reveal that effective leadership plays a central role in driving service innovation. Leaders at UIN SUSKA Riau demonstrate strategic vision and the ability to communicate and operationalize innovative ideas to improve academic services. Efforts include the implementation of digital platforms (e.g., e-learning systems, academic portals), routine staff development programs, and the decentralization of support systems across faculties. However, challenges remain in standardizing services, resource allocation, and integrating IT systems across departments. This study underscores the importance of leadership commitment, digital transformation, and human resource development in enhancing educational support services. Strengthening these elements can foster a more responsive and efficient academic environment. Innovative leadership and systemic improvements in instructional and administrative services are essential for enhancing the quality of higher education delivery.